The Sacred Motif in the Poems of Magzhan Zhumabayuly - Aimukhambet Ж.Ә.; Mirazova М.Н.; Rakhmetova Б.А. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
This article explores the manifestation of the concepts kie, tylsym (mystery), and sacredness, which stem from ancient beliefs and remain embedded in collective consciousness, through the poetic works of Magzhan Zhumabayev. The discussion begins with an overview of definitions and interpretations of kie, emphasizing its cognitive foundations and artistic significance. In the Kazakh worldview, kie represents a mystical force attributed not only to natural sites and phenomena—mountains, land, water, caves—but also to animals, birds, and exceptional individuals. Having evolved from mythological narratives into folklore and later into written literature, sacred motifs acquired diverse aesthetic and cognitive functions. These are vividly exemplified in Zhumabayev’s poems Batyr Bayan, Korkyt, The Koby of Koilybay, and On the Cliff of Okzhetpes. In Batyr Bayan, the sacred motif is embodied in Abylai Khan, whose spiritual strength was believed to strike down opponents, and in Burabay, his symbolic stronghold. In Korkyt, sacredness emerges through the Altai Mountains and Korkyt-ata; in The Koby of Koilybay—through the shaman Koilybay with his mystical powers; and in On the Cliff of Okzhetpes—through Pir-baba, aligning with the poet’s worldview. The article demonstrates how sacred motifs serve both as artistic devices and as cultural codes, preserving the spiritual heritage and historical memory of the Kazakh people.